PENINGKATAN PEMAHAMAN KONSEP PESERTA DIDIK MELALUI MEDIA KIT COVALENT CREATOR BERBASIS MULTIREPRESENTASI - Aras Hidayat; Eny Enawaty; Lukman Hadi (Universitas Tanjungpura, 2022)
Many students face difficulty in learning chemical bonding. This study was conducted to examine the effect of a Covalent Creator KIT media on students' conceptual understanding. Research design used is quasi-experiment research with a nonequivalent control group design. Subjects in this research were 64 students of Senior High School 1 Pontianak. The sampling technique used was cluster random sampling technique. Data collection tools were tests of students’ conceptual understanding and interviews. The data analysis result showed that representation there were significant differences in understanding concepts in students taught using the Covalent Creator KIT media and students taught using student worksheets. The use of Covalent Creator KIT media on covalent bond material learning gives an effect of 51.6% on the students' conceptual understanding.